Composition and vinyl polymer

A vinyl compound composition with specific formulations and additives addresses the issues of high viscosity and low refractive index in conventional diluents, achieving low viscosity, high refractive index, and excellent curability and adhesion for use in optical materials.

JP7665569B2Active Publication Date: 2025-04-21JFE CHEMICAL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022139798
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-04-21
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

Conventional vinyl compound diluents have high viscosity, which affects wettability, and low refractive index, making them unsuitable for optical materials, while also lacking excellent curability and adhesion.

Method used

A composition of vinyl compounds (A) and (B) with specific mass ratios, viscosity ranges, and the inclusion of a polymerization initiator, which forms a vinyl polymer with low viscosity, high refractive index, and excellent curability and adhesion.

Benefits of technology

The composition achieves low viscosity and high refractive index, along with excellent curability and adhesion, making it suitable for use in optical materials and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665569000001
    Figure 0007665569000001
  • Figure 0007665569000002
    Figure 0007665569000002
  • Figure 0007665569000003
    Figure 0007665569000003
Patent Text Reader

Abstract

To provide a composition that has low viscosity and a high refractive index and also has excellent curability and adhesion.SOLUTION: A composition comprises a vinyl compound (A) represented by a formula (1), and a vinyl compound (B) represented by a formula (2). In the formula (2), n is 1, 2 or 3.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition and a vinyl polymer. [Background technology]

[0002] From the viewpoints of safety and hygiene, etc., a mixture of vinyl compounds may be used as a diluent instead of a solvent in order to avoid the use of solvents (Patent Documents 1 to 3). The mixture of vinyl compounds as a diluent is reactive (curable) in itself and is used without a solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-037548 A [Patent Document 2] JP 2003-226719 A [Patent Document 3] JP 2005-60393 A Summary of the Invention [Problem to be solved by the invention]

[0004] Like a solvent, a diluent is combined with a base material and applied to a substrate, etc. For this reason, when a vinyl compound mixture is used as a diluent, it is required to have a low viscosity from the viewpoint of ensuring wettability to the substrate, etc. In addition, many conventional diluents lower the refractive index of the base material, making it difficult to apply them to optical materials (displays, sensors, etc.). For this reason, diluents with a high refractive index are desired. Further, as basic properties, the diluent is required to have good curability as well as good adhesion to the substrate.

[0005] Therefore, an object of the present invention is to provide a composition (a mixture of vinyl compounds) which has a low viscosity and a high refractive index, and also has excellent curability and adhesive properties. [Means for solving the problem]

[0006] As a result of extensive investigations, the present inventors have found that the above object can be achieved by employing the following configuration, and have completed the present invention.

[0007] That is, the present invention provides the following [1] to [7]. [1] A composition containing a vinyl compound (A) represented by the formula (1) described below and a vinyl compound (B) represented by the formula (2) described below. [2] The composition according to the above [1], wherein a mass ratio (A / B) of the vinyl compound (A) to the vinyl compound (B) is 5 / 95 to 75 / 25. [3] The composition according to the above [1] or [2], having a viscosity at 20°C of 3 to 50 mPa s. [4] The composition according to any one of the above [1] to [3], which contains a polymerization initiator. [5] The composition according to [4] above, wherein the content of the polymerization initiator is 0.3 to 5.0 parts by mass per 100 parts by mass of the total of the vinyl compound (A) and the vinyl compound (B). [6] A vinyl polymer obtained by polymerizing a vinyl compound (A) represented by the formula (1) described below and a vinyl compound (B) represented by the formula (2) described below. [7] The vinyl polymer according to the above [6], wherein a mass ratio (A / B) of the vinyl compound (A) to the vinyl compound (B) is 5 / 95 to 75 / 25. Effect of the Invention

[0008] According to the present invention, it is possible to provide a composition (mixture of vinyl compounds) which has a low viscosity and a high refractive index, and also has excellent curability and adhesive properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The composition (mixture of vinyl compounds) of the present invention will be described below. The following description also includes the description of the vinyl polymer of the present invention.

[0010] [Composition] The composition of the present invention is a mixture of vinyl compounds, and more specifically, contains a vinyl compound (A) and a vinyl compound (B) described below. The composition of the present invention has a low viscosity and a high refractive index, and also has excellent curability and adhesive properties.

[0011] <Vinyl compound (A)> The vinyl compound (A) is a monofunctional vinylnaphthalene represented by the following formula (1). The vinyl compound (A) has positional isomers, and may be used alone or in combination of two or more. Specific examples of positional isomers include 1-vinylnaphthalene and 2-vinylnaphthalene.

[0012] [ka]

[0013] <Vinyl Compounds (B)> The vinyl compound (B) is a vinyl ether having an ethylene glycol group and a biphenyl group, represented by the following formula (2).

[0014] [ka]

[0015] In the above formula (2), n represents 1, 2 or 3. When n=1, the vinyl compound (B) is 2-(vinyloxyethoxy)biphenyl (other name: phenylphenoxyethyl vinyl ether). When n=2, the vinyl compound (B) is 2-(vinyloxyethoxy)ethoxybiphenyl. When n=3, the vinyl compound (B) is 2-[2-(2-vinyloxyethoxy)ethoxy]biphenyl. The vinyl compound (B) may be a single compound or a mixture of multiple compounds.

[0016] <viscosity> When the composition of the present invention does not contain any component other than the vinyl compound (A) and the vinyl compound (B), its viscosity is, for example, 50 mPa·s or less. The viscosity of the composition of the present invention is, for example, 3 to 50 mPa·s, and from the viewpoint of wettability to a substrate such as glass, it is preferably 5 to 30 mPa·s. The viscosity is measured using a rotational viscometer at 20° C. More specifically, the viscosity is measured by the method described in the Examples section below.

[0017] <Mass ratio> The mass ratio (A / B) of the vinyl compound (A) to the vinyl compound (B) is preferably from 5 / 95 to 75 / 25, and more preferably from 30 / 70 to 70 / 30, because this brings the viscosity of the composition of the present invention into the above-mentioned range.

[0018] <Polymerization initiator> The composition of the present invention may further contain a polymerization initiator. The polymerization initiator is not particularly limited as long as it activates the olefin moieties of the vinyl compound (A) and the vinyl compound (B), and any generally known initiator may be used. For example, examples of the initiator include a thermally decomposable radical generator having an azo structure; an intramolecular cleavage type initiator such as a hydroxyalkylphenone, an acylphosphine oxide, or an oxime ester; an intramolecular hydrogen abstraction type initiator; a Bronsted acid generation type initiator; and an onium salt initiator such as an iodonium salt, a sulfonium salt, a selenonium salt, a phosphonium salt, a diazonium salt, or an antimony hexafluoride salt. These initiators may be used alone or in combination of two or more kinds.

[0019] The content of the polymerization initiator is preferably from 0.3 to 5.0 parts by mass, and more preferably from 1.0 to 3.0 parts by mass, based on 100 parts by mass in total of the vinyl compound (A) and the vinyl compound (B).

[0020] <Other Ingredients> The composition of the present invention may contain, if necessary, other polymerizable olefins; cyclic ethers such as epoxy and oxetane; organopolysiloxanes; and the like. Furthermore, to the composition of the present invention, an adhesion improver for improving adhesion to a substrate, a leveling agent, an antistatic agent, a high flexural modifier, a flame retardant, an antifoaming agent, a pigment, a filler, talc, etc. may be added as necessary. The composition of the present invention is intended to be used without a solvent, but may also be used after diluting with an organic solvent.

[0021] <Preparation> The method for preparing the composition of the present invention is not particularly limited. For example, it can be easily prepared by mixing the vinyl compound (A), the vinyl compound (B), and a polymerization initiator, and further, if necessary, other components. These components may be mixed simultaneously, or the vinyl compound (A) and the vinyl compound (B) may be mixed together and then the polymerization initiator may be added.

[0022] For example, a vinyl polymer (for example, a cured film described later) is obtained by polymerizing a vinyl compound (A) and a vinyl compound (B) by the action of a polymerization initiator.

[0023] Coating and curing The composition of the present invention is, for example, applied to a substrate, thereby obtaining a coating film. The coating method is not particularly limited, and examples thereof include known coating methods such as roll coating, gravure coating, die coating, wire doctor coating, spraying, mist spraying, dipping, and ink jet.

[0024] The substrate to which the composition of the present invention is applied is not particularly limited, and examples thereof include films, sheets, and molded articles. The material of the substrate is not particularly limited, and examples thereof include metals such as steel, copper, and aluminum; synthetic resins; glass; and carbon fiber; and is appropriately selected depending on the application.

[0025] The resulting coating film is cured, thereby obtaining a cured film. The method for curing the coating film is not particularly limited, and examples thereof include a method of curing the coating film by heating or by irradiating it with ultraviolet light. For example, devices used for heating (heating devices) include hot air dryers, far-infrared heaters, and heating furnaces. Examples of the light source for the ultraviolet irradiation device include a high-pressure mercury lamp, a medium-pressure mercury lamp, a low-pressure mercury lamp, a metal halide lamp, a mercury arc lamp, a light-emitting diode, etc. For example, when using a high-pressure mercury lamp (80 W / cm), irradiation is performed from a distance of 5 to 20 cm for 0.01 to 30 seconds.

[0026] <Application> The composition of the present invention has a low viscosity and can be used as a diluent. In this case, the composition is used in combination with a base agent (for example, a known resin component). By coating and curing the composition of the present invention, a cured film having excellent transparency and a high refractive index can be easily obtained. Therefore, the composition of the present invention can be used, for example, as a top coat or intermediate layer for displays, sensor lenses, etc.; a protective coating agent for metals, plastics, etc.; etc. However, the use of the composition of the present invention is not limited to these uses. EXAMPLES

[0027] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples described below.

[0028] Example 1 5.0 g of 1-vinylnaphthalene (1-VN), 1.0 g of 2-vinylnaphthalene (2-VN), and 4.0 g of 2-(vinyloxyethoxy)biphenyl (n=1 in formula (2)) (BP-EG-VE) were placed in a light-shielded glass bottle and mixed for 2 hours using a shaker with the outside temperature controlled at 23±1° C. to obtain 10.0 g of a colorless, transparent solution. The resulting solution was used as the test solution of Example 1.

[0029] Example 2 2.5 g of 1-vinylnaphthalene, 2.5 g of 2-vinylnaphthalene, and 5.0 g of 2-(vinyloxyethoxy)biphenyl (n=1 in formula (2)) were placed in a light-shielded glass bottle and mixed for 2 hours using a shaker with the outside temperature controlled at 23±1°C to obtain 10.0 g of a colorless, transparent solution. The resulting solution was used as the test liquid for Example 2.

[0030] Example 3 4.0 g of 1-vinylnaphthalene and 6.0 g of 2-(vinyloxyethoxy)biphenyl (n=1 in formula (2)) were placed in a light-shielded glass bottle and mixed for 2 hours using a shaker with the outside temperature controlled at 23±1°C to obtain 10.0 g of a colorless, transparent solution. The resulting solution was used as the test liquid for Example 3.

[0031] Example 4 2.5 g of 1-vinylnaphthalene, 1.5 g of 2-vinylnaphthalene, and 6.0 g of 2-(vinyloxyethoxy)biphenyl (n=1 in formula (2)) were placed in a light-shielded glass bottle and mixed for 2 hours using a shaker with the outside temperature controlled at 23±1°C to obtain 10.0 g of a colorless, transparent solution. The resulting solution was used as the test liquid for Example 4.

[0032] Comparative Example 1 7.0 g of 1-vinylnaphthalene and 3.0 g of 2-vinylnaphthalene were placed in a light-shielded glass bottle and mixed for 2 hours using a shaker with the outside temperature controlled at 23±1° C. to obtain 10.0 g of a colorless, transparent solution. The obtained solution was used as the test liquid of Comparative Example 1.

[0033] Comparative Example 2 Into a light-shielded glass bottle was placed 10.0 g of 2-(vinyloxyethoxy)biphenyl ((n=1 in formula (2)) and this was used as the test liquid of Comparative Example 2.

[0034] Comparative Example 3 Into a light-shielded glass bottle was placed 10.0 g of 2-(2-vinyloxyethoxy)ethyl acrylate, which was used as the test liquid of Comparative Example 3.

[0035] Comparative Example 4 Into a light-shielded glass bottle was placed 10.0 g of methyl 2-(allyloxymethyl)acrylate, which was used as the test liquid of Comparative Example 4.

[0036] Comparative Example 5 Into a light-shielded glass bottle, 10.0 g of vinyl methacrylate was placed, and this was used as the test liquid of Comparative Example 5.

[0037] <evaluation> The tests described below were carried out to evaluate various properties using the test solutions of Examples 1 to 4 and Comparative Examples 1 to 5. The results are shown in Table 1 below.

[0038] "viscosity" The glass bottle containing the test liquid was placed in a thermostatic bath and the temperature of the contents (test liquid) was adjusted to 20°C. The rotor LV-1 attached to a Brookfield viscometer (DVIIIULTRA, Brookfield) was operated at a rotation speed of 60 rpm for 30 seconds, after which the viscosity of the test liquid (unit: mPa s) was measured.

[0039] Refractive Index The refractive index (nD25) of the test liquid at 25° C. was measured using an Abbe refractometer (manufactured by Atago Co., Ltd.) in accordance with JIS K 7105. The refractive index of the polymer obtained by polymerizing the polymerization component (vinyl compound) contained in the test liquid is 0.04 to 0.05 higher than the refractive index of the test liquid.

[0040] 《Curability》 (Coating) 0.2 g of a photosensitive polymerization initiator (CPI-210S, San-Apro Co., Ltd.) was added to 10.0 g of the test liquid, and dissolution of the polymerization initiator was confirmed. Then, the test liquid was placed on a glass plate (slide glass S9112, Matsunami Glass Industry Co., Ltd.), and a coating film of about 50 μm in thickness was formed using a doctor blade (2 mil, Yasuda Seiki Seisakusho Co., Ltd.) to obtain a test panel.

[0041] (hardening) The obtained test panel was exposed to ultraviolet light for 20 seconds using a UV irradiator equipped with a high-pressure mercury lamp (Unicure System UVC-1212, manufactured by Ushio Inc.) to cure the coating film.

[0042] (Evaluation Criteria) The cured coating film was touched with a finger and the curability was evaluated according to the following criteria. If the coating surface had lost its tackiness (stickiness), it was marked with "○", and if the coating did not harden and remained liquid or if the coating surface still had a tackiness (stickiness), it was marked with "×" in Table 1. If it was marked with "○", it could be evaluated as having excellent curability.

[0043] 《Adhesiveness》 For the test panels for which the evaluation result of curability was "○", a cutter knife was inserted between the cured coating film (cured film) and the glass plate, and force was applied with fingers to peel them off (expose the interface). If there was sufficient resistance when peeled off and the interface could not be exposed (the cured film did not peel off), it was marked with "○", and if the interface could be exposed (the cured film peeled off), it was marked with "×", both of which are shown in Table 1. If it is marked with "○", it can be evaluated as having excellent adhesion.

[0044] [Table 1]

[0045] <Summary of evaluation results> As shown in Table 1 above, the test liquids of Examples 1 to 4 had low viscosity and high refractive index, and also had good curability and adhesiveness. In contrast, the test liquid of Comparative Example 1 had insufficient adhesiveness. The test liquid of Comparative Example 2 had a higher viscosity than those of Examples 1-4. The test liquid of Comparative Example 3 had a lower refractive index than those of Examples 1-4. The test liquids of Comparative Examples 4 to 5 had a lower refractive index than those of Examples 1 to 4, and the curability was insufficient.

Claims

1. A composition comprising a vinyl compound (A) represented by the following formula (1) and a vinyl compound (B) represented by the following formula (2): 【Chemistry 1】 【change】 In the formula (2), n represents 1, 2 or 3.

2. The composition according to claim 1, wherein a mass ratio (A / B) of the vinyl compound (A) to the vinyl compound (B) is 5 / 95 to 75 / 25.

3. 3. The composition according to claim 1, having a viscosity at 20° C. of 3 to 50 mPa·s.

4. The composition according to claim 1 or 2, which contains a polymerization initiator.

5. The composition according to claim 4, wherein the content of the polymerization initiator is 0.3 to 5.0 parts by mass per 100 parts by mass of the total of the vinyl compound (A) and the vinyl compound (B).

6. A vinyl polymer obtained by polymerizing a vinyl compound (A) represented by the following formula (1) and a vinyl compound (B) represented by the following formula (2). 【Chemistry 2】 【change】 In the formula (2), n represents 1, 2 or 3.

7. The vinyl polymer according to claim 6, wherein the mass ratio (A / B) of the vinyl compound (A) to the vinyl compound (B) is 5 / 95 to 75 / 25.

Citation Information

Patent Citations

  • Resin having high refractive index and excellent heat resistance for optical material

    JP1996053517A

  • High refractive index resin composition for coating and its cured product

    JP2003026889A

  • (Meth)Acrylate type copolymer having vinyl ether group and its production method

    JP2003226719A

  • Production method for high-purity (METH)acryloyloxyalykyl isocyanate

    JP2005060393A

  • High refractive index resin for optical material, high refractive index resin composition for optical material, and cured product using the same

    JP2009191159A